The Semantic Turn : a New Foundation for Design. - Krippendorff, Klaus (Taylor and Francis, 2004)
Responding to cultural demands for meaning, user-friendliness, and fun as well as the opportunities of the emerging information society, The Semantic Turn boldly outlines a new science for design that gives designers previously unavailable grounds on which to state their claims and validate their designs. It sets the stage by reviewing the history of semantic concerns in design, presenting their philosophical roots, examining the new social and technological challenges that professional designers are facing, and offering distinctions among contemporary artifacts that challenge designers.